Evaluation of Concept Mastery and Representation Skills Assessment in High School on Nervous System Material - Mia Angriana Juniarti; Yanti; Saefudin (Al Jahiz, 2025)
Learning demands that students not only memorize facts but also understand concepts in depth to be able to accurately represent scientific phenomena. This research aims to produce a valid assessment of concept mastery and representation skills. This research used descriptive quantitative method with a total of 60 Grade XI students who had received nervous system material. The validity instrument test of concept mastery and representation skills were analyzed based on logical validity and empirical validity. The results of the logical validity of concept mastery questions by expert validator lecturer of 92.69% and biology teacher of 100% indicate that this instrument is highly valid to measure student understanding of nervous system material. The results of the logical validity of the representation skills question by expert validator lecturer of 73.10% and biology teacher of 100% indicate that the test instrument is valid to measure students' representation skills, but moderate revisions are needed. On the other hand, results of empirical validity show that multiple choice questions have a validity of 0.56 and reliability of 0.72, while essay questions have a validity of 0.46 and reliability of 0.63. Thus, the instruments test of concept mastery and representation skills of nervous system material fall into the moderately valid to highly valid category.